Construction and standardisation of an instrument measuring lecturers’ persistence to publish in Scopus-indexed journals (Journal of Applied Learning and Teaching, 2023)
Academic publishing is a critical aspect of research, contributing to knowledge dissemination and career advancement. However, there is a paucity of standardised instruments for assessing academics’ persistence in publishing. This study developed and validated the Persistence to Publish Questionnaire (PPQ) as a valid and reliable tool for evaluating academics’ persistence to publishing in Scopus-indexed journals. The PPQ was developed through a rigorous process, including item generation, content validity assessment, pretesting, and pilot testing of items. A sample of academics (n = 262) from various disciplines across two public universities in Cross River State participated in the validation process. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were conducted to determine the instrument’s factor structure and evaluate its fit. The results from the analysis revealed that the PPQ is a multidimensional instrument with five underlying factors – persistence in manuscript preparation, manuscript submission, handling revisions, dealing with rejections, and publication delays. The PPQ exhibited strong reliability in terms of internal consistency, with Cronbach’s α values ranging from .89 to .99. McDonald’s ω and split-half reliability corrected with the Spearman-Brown prophecy formula (rtt) results further supported its reliability. Construct validity evidence showed both convergent and discriminant validity, confirming that the PPQ effectively measures persistence to publish. The PPQ represents a valuable contribution to the field of academic publishing. It offers an opportunity for researchers and institutions to assess the degree to which academics are willing to publish, empowering researchers and institutions to identify areas of improvement and provide targeted support. This tool holds promise for enhancing research productivity and quality within the global academic community.